Emerging Roles of m6A RNA Methylation Regulators in Gynecological Cancer - Huang, Wanjun; Kong, Fanhua; Li, Ruolan; Chen, Xiang; Wang, Kunpeng (Frontiers in Oncology, 2022)
Gynecological cancers seriously affect the reproductive system of females; diseases include ovarian tumors, uterine tumors, endometrial cancers, cervical cancers, and vulva and vaginal tumors. At present, the diagnosis methods of gynecological cancer are insufficiently sensitive and specific, leading to failure of early disease detection. N6-methyladenosine (m6A) plays various biological functions in RNA modification and is currently studied extensively. m6A modification controls the fate of transcripts and regulates RNA metabolism and biological processes through the interaction of m6A methyltransferase (“writer”) and demethylase (“erasers”) and the binding protein decoding m6A methylation (“readers”). In the field of epigenetics, m6A modification is a dynamic process of reversible regulation of target RNA through its regulatory factors. It plays an important role in many diseases, especially cancer. However, its role in gynecologic cancers has not been fully investigated. Thus, we review the regulatory mechanism, biological functions, and therapeutic prospects of m6A RNA methylation regulators in gynecological cancers.